Analisis Strategi Pelayanan Jamaah Haji dan Umrah dalam Membangun Reputasi PT. Anugerah Quba Mandiri - Bagus Piansyah; Yosy Arisandi; Khozin Zaki (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the service strategy for Hajj and Umrah pilgrims, service quality, and reputation-building efforts of PT. Anugerah Quba Mandiri as a Hajj and Umrah travel agency. The research employed a qualitative approach using field research methods. Data were collected through in-depth interviews, observations, and documentation involving managers, supervisors, customer service staff, and Umrah pilgrims. Data analysis was conducted using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that PT. Anugerah Quba Mandiri implements a systematic service strategy, starting from service planning at the registration stage, transparent package information, well-planned departure schedules, and continuous evaluation through communication with pilgrims. The service quality meets the SERVQUAL dimensions, including tangibles, reliability, responsiveness, assurance, and empathy, contributing to pilgrim satisfaction and comfort. Reputation building is achieved through regulatory compliance, professional service delivery, consistency between promises and service realization, and the implementation of sustainable social responsibility programs. These results demonstrate that the integration of service strategy and service quality plays a crucial role in building and maintaining corporate reputation in a sustainable manner.